English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

What is the solution set of the equation x = 2 sqroot (2x-3)?

a.) {2,6}
b.) { }
c.) {6}
d.) {2}

2007-04-03 12:05:14 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

x = 2 sqrt(2x - 3)

To solve this, first square both sides.

x^2 = 4 (2x - 3)
x^2 = 8x - 12
x^2 - 8x + 12 = 0

Now, factor.

(x - 6)(x - 2) = 0

Therefore, x = {2, 6}. However, we must always check for extraneous solutions by plugging into the original equation,
x = 2sqrt(2x - 3).

Let x = 2. Does

2 = 2sqrt(2(2) - 3) ?
2 = 2sqrt(4 - 3) ?
2 = 2sqrt(1) ?
2 = 2(1) ?
2 = 2 ? YES!

Let x = 6. Does

6 = 2sqrt(2(6) - 3) ?
6 = 2sqrt(12 - 3) ?
6 = 2sqrt(9) ?
6 = 2(3) ?
6 = 6? YES!

Therefore, x = {2, 6}

2007-04-03 12:09:48 · answer #1 · answered by Puggy 7 · 0 0

3,-2(c7d6c844b493f458dbeae5f3fec58efxc7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58ef)² = 5c7d6c844b493f458dbeae5f3fec58ef (c7d6c844b493f458dbeae5f3fec58efxc7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58ef)² =5c7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58ef (c7d6c844b493f458dbeae5f3fec58efxc7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58ef)² =c7d6c844b493f458dbeae5f3fec58ef5 Taking sq. roots the two facets: c7d6c844b493f458dbeae5f3fec58efxc7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58ef =±5 If c7d6c844b493f458dbeae5f3fec58efxc7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58ef =+5c7d6c844b493f458dbeae5f3fec58ef then c7d6c844b493f458dbeae5f3fec58efx=5+3,-2 c7d6c844b493f458dbeae5f3fec58efx=6 x=6c7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58ef x=3,-2 and if c7d6c844b493f458dbeae5f3fec58efxc7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58ef =c7d6c844b493f458dbeae5f3fec58ef5c7d6c844b493f458dbeae5f3fec58ef thenc7d6c844b493f458dbeae5f3fec58ef c7d6c844b493f458dbeae5f3fec58efxc7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58ef =c7d6c844b493f458dbeae5f3fec58ef5c7d6c844b493f458dbeae5f3fec58ef c7d6c844b493f458dbeae5f3fec58efx=c7d6c844b493f458dbeae5f3fec58ef5+3,-2 c7d6c844b493f458dbeae5f3fec58efx=c7d6c844b493f458dbeae5f3fec58ef4 x=c7d6c844b493f458dbeae5f3fec58ef4c7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58ef x=c7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58ef So the solutions is : Bc7d6c844b493f458dbeae5f3fec58ef [c7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58ef] c7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58efc7d6c844b493f458dbeae5f3fec58ef

2016-11-26 00:12:23 · answer #2 · answered by ? 4 · 0 0

x = 2 sqroot (2x-3)?
x^2 =4(2x-3) = 8x - 12
x^2-8x+12 = 0
(x-6)(x-2) =0
So x = 2 and x=2
Answer is {2,6}

2007-04-03 12:19:21 · answer #3 · answered by ironduke8159 7 · 0 0

x^2=8x-12
x^2-8x+12=0
x^2-6x-2x+12=0
x(x-6)-2(x-6)=0
(x-6)(x-20=0
x=6,2

2007-04-03 12:12:42 · answer #4 · answered by Gladiator 2 · 0 0

fedest.com, questions and answers